Algebra 1 (2008)
We shall expose the meaning of a set and state the different ways of naming a set. We shall also reveal the different types of sets, subsets, equality of sets and the universe of discourse. We shall then interact various sets which belong to the same universe, using the definitions of union, intersection, power set, complements, relative complements and symmetric difference to form new sets. Geometry representation of sets shall be presented in the form of Venn diagrams which will then be used in solving problems on sets. We also study some similarities of algebra of numbers to algebra of set theory and give a theorem on the number of elements in sets